A bioinspired glycopolymer for capturing membrane proteins in native-like lipid-bilayer nanodiscs. Issue 5 (18th January 2022) - Danielczak, Bartholomäus; Rasche, Marie; Lenz, Julia; Pérez Patallo, Eugenio; Weyrauch, Sophie; Mahler, Florian; Agbadaola, Michael Tope; Meister, Annette; Babalola, Jonathan Oyebamiji; Vargas, Carolyn; Kolar, Cenek; Keller, Sandro
Abstract : The bioinspired glycosylated polymer Glyco-DIBMA outperforms other polymers in efficiently extracting membrane proteins and lipids into well-defined, native-like lipid-bilayer nanodiscs. Abstract : Amphiphilic copolymers that directly extract membrane proteins and lipids from cellular membranes to form nanodiscs combine the advantages of harsher membrane mimics with those of a native-like membrane environment. Among the few commercial polymers that are capable of forming nanodiscs, alternating diisobutylene/maleic acid (DIBMA) copolymers have gained considerable popularity as gentle and UV-transparent alternatives to aromatic polymers. However, their moderate hydrophobicities and high electric charge densities render all existing aliphatic copolymers rather inefficient under near-physiological conditions. Here, we introduce Glyco-DIBMA, a bioinspired glycopolymer that possesses increased hydrophobicity and reduced charge density but nevertheless retains excellent solubility in aqueous solutions. Glyco-DIBMA outperforms established aliphatic copolymers in that it solubilizes lipid vesicles of various compositions much more efficiently, thereby furnishing smaller, more narrowly distributed nanodiscs that preserve a bilayer architecture and exhibit rapid lipid exchange. We demonstrate the superior performance of Glyco-DIBMA in preparative and analytical applications by extracting a broad range of integral membrane proteins from cellular membranes and further by purifying a membrane-embedded voltage-gated K + channel, which was fluorescently labeled and analyzed with the aid of microfluidic diffusional sizing (MDS) directly within native-like lipid-bilayer nanodiscs.